2013
DOI: 10.1016/j.jnutbio.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA damage and repair in adults consuming allyl isothiocyanate or Brassica vegetables

Abstract: Allylisothiocyanate (AITC) is a dietary component with possible anti-cancer effects, though much information about AITC and cancer has been obtained from cell studies. To investigate the effect of AITC on DNA integrity in vivo, a crossover study was conducted. Adults (n=46) consumed AITC, AITC-rich vegetables (mustard and cabbage), or a control treatment with a controlled diet for 10 days each. On day 11, volunteers provided blood and urine before and after consuming treatments. Volunteers were characterized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Similarly, other studies showed that Brassica plants did not affect DNA integrity of mouse cells [67]. Human population studies revealed that high doses of ITC may lead to short-term DNA damage, but this was reversed quickly by DNA base excision repair [68]. In terms of consumer safety, derivatives of indolic neo-GBS that form DNA adducts with high efficiency, should in longterm perspective be avoided, at least until their safety is not unequivocally confirmed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, other studies showed that Brassica plants did not affect DNA integrity of mouse cells [67]. Human population studies revealed that high doses of ITC may lead to short-term DNA damage, but this was reversed quickly by DNA base excision repair [68]. In terms of consumer safety, derivatives of indolic neo-GBS that form DNA adducts with high efficiency, should in longterm perspective be avoided, at least until their safety is not unequivocally confirmed.…”
Section: Discussionmentioning
confidence: 95%
“…acephala) did not induce DNA strand breaks in mouse cells, neither was genotoxic [67]. Human studies showed that ITC and ITC-rich products induced DNA damage upon shortterm treatment, but that damage disappeared quickly and without affecting DNA base excision repair [68].…”
Section: Dna Fragmentation In Eukaryotic Cell Culturementioning
confidence: 94%
“…Scaled for body weight, the daily intake of Brussels sprouts was similar to the intake of broccoli in the present study (25·6 vs 17·3 g kg −1 body weight). In a recent human study, Charron et al . reported a transient increase in DNA damage in peripheral blood mononuclear cells isolated from individuals 3 h after they had consumed either isolated allyl isothiocyanate (114·7 µmol) incorporated into mayonnaise or a mustard/cabbage treatment (150 g of raw homogenized cabbage plus 30 g of Grey Poupon Country Dijon Mustard).…”
Section: Discussionmentioning
confidence: 99%
“…Scaled for body weight, the daily intake of Brussels sprouts was similar to the intake of broccoli in the present study (25·6 vs 17·3 g kg À1 body weight). In a recent human study, Charron et al 56 reported a transient increase in DNA damage in peripheral blood mononuclear cells isolated from individuals 3 h after they had consumed either isolated allyl isothiocyanate (114·7 μmol) incorporated into mayonnaise or a mustard/cabbage treatment (150 g of raw homogenized cabbage plus 30 g of Grey Poupon Country Dijon Mustard). In contrast, the majority of studies in humans have reported that modest intakes of raw and cooked cruciferous vegetables (85-300 g day À1 ) protect lymphocytes from DNA damage or reduce the urinary excretion of 8-oxo-dG 57-62 (a possible marker of whole body oxidative stress).…”
Section: Discussionmentioning
confidence: 99%
“…AITC, when provided in diet, exhibited short-term reversible DNA damage [101]. This may explain the anticancer effects exerted by AITC, as cancer cells are more susceptible to DNA damage mediated induction of apoptosis.…”
Section: Allyl Isothiocyanatementioning
confidence: 98%